Emergence of meaning, signals and the concept of consciousness - Esteban Céspedes (Filosofia Unisinos)
Following an account of signaling games, one can show how meaning emerges and is preserved on the basis of the interactions between individuals and their environments. It is here argued that, as all concepts, a concept of consciousness is formed from a set of signaling games and is assigned a sense, from which its extensional reference can be postulated. It will be helpful to understand the contrast between what we may call a representationalist account of consciousness and an enactivist account. As argued, a consciousness state can be assumed and fixed by intensional reference. Thus, although the notion of consciousness may be explanatorily excluded, in principle, from a neurobiological language, it remains relevant in a semantic way. This is a consequence of what we may call the semantic gap between the mental and the physical.